Rescue of the spinal muscular atrophy phenotype in a mouse model by early postnatal delivery of SMN - Foust, Kevin D (2010)
Spinal muscular atrophy (SMA), the most common autosomal recessive neurodegenerative disease affecting children, results in impaired motor neuron function1. Despite knowledge of the pathogenic role of decreased survival motor neuron (SMN) protein levels, efforts to increase SMN have not resulted in a treatment for patients. We recently demonstrated that self-complementary adeno-associated virus 9 (scAAV9) can infect ~60% of motor neurons when injected intravenously into neonatal mice2–4. Here we use scAAV9-mediated postnatal day 1 vascular gene delivery to replace SMN in SMA pups and rescue motor function, neuromuscular physiology and life span. Treatment on postnatal day 5 results in partial correction, whereas postnatal day 10 treatment has little effect, suggesting a developmental period in which scAAV9 therapy has maximal benefit. Notably, we also show extensive scAAV9-mediated motor neuron transduction after injection into a newborn cynomolgus macaque. This demonstration that scAAV9 traverses the blood-brain barrier in a nonhuman primate emphasizes the clinical potential of scAAV9 gene therapy for SMA.